Reusable Heterogeneous Catalyst (M2+)Al-Layered Double Hydroxide used for Oxidative Desulfurization of 4,6-Dimethyldibenzothiophene - Nur Ahmad; Sahrul Wibiyan; Idha Royani; Risfidian Mohadi; Aldes Lesbani (Indonesian Journal of Material Research, 2023)
Catalyst material (M2+)Al-LDH was successfully prepared in this study. Characterisation analysis by XRD and FTIR. XRD analysis of Zn/Al-LDH, Mg/Al-LDH and Ni/Al-LDH showed agreement with pure LDH as seen from the JCPDS data and showed crystal forms similar to hydrotalcite, brucite and hydrotalcite respectively. FTIR analysis of the (M2+)Al-LDH material showed the presence of functional groups which explain the presence of O-H stretching, O-H bending, CO32- bonds and identified metal oxide (MO) groups from the synthesised LDH. (M2+)Al-LDH has the ability to act as a catalyst for excellent desulphurisation of 4,6-dimethyldibencothiophene with % conversion value above 90%. In addition, (M2+)Al-LDH is a heterogeneous and reusable catalyst.